2014
DOI: 10.1002/jat.3008
|View full text |Cite
|
Sign up to set email alerts
|

In vitro exposure of DE‐71, a penta‐PBDE mixture, on immune endpoints in bottlenose dolphins (Tursiops truncatus) and B6C3F1 mice

Abstract: Polybrominated diphenyl ethers (PBDEs) are an emerging contaminant of concern with low level exposures demonstrating toxicity in laboratory animals and wildlife, although immunotoxicity studies have been limited. Bottlenose dolphin peripheral blood leukocytes (PBLs) and mouse splenocytes were exposed to environmentally relevant DE-71 (a penta-PBDE mixture) concentrations (0-50 µg ml(-1) ) in vitro. Natural killer (NK) cell activity and lymphocyte (B and T cell) proliferation were evaluated using the parallelog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…Our experiments were performed in serum-free conditions and thus the free PBDE concentrations may be lower in vivo where serum binding proteins for PBDE are present. The concentration range of DE-71 used in this study were similar to former in vitro studies with PBDEs [61;62]. The lowest concentration of DE-71 used in our study was 0.01 mg DE-71/L.…”
Section: Discussionsupporting
confidence: 83%
“…Our experiments were performed in serum-free conditions and thus the free PBDE concentrations may be lower in vivo where serum binding proteins for PBDE are present. The concentration range of DE-71 used in this study were similar to former in vitro studies with PBDEs [61;62]. The lowest concentration of DE-71 used in our study was 0.01 mg DE-71/L.…”
Section: Discussionsupporting
confidence: 83%
“…Although these PBDEs have been phased out, some PBDE congeners are still being detected in the environment including soil, sediment, air, water, and biota . In addition, many of these PBDEs are bioaccumulated in humans and wildlife through the food chain owing to their high persistency and lipophilicity. , Previous studies have focused on various toxic effects induced by PBDEs, such as developmental toxicology, , neurotoxicity, , immunotoxicity, , and endocrine disruption. , It has been suggested that these adverse effects may be mediated by estrogen receptor (ER), , aryl hydrocarbon receptor (AhR), , constitutive active/androstane receptor (CAR), and pregnane X receptor (PXR) …”
Section: Introductionmentioning
confidence: 99%
“…The chosen concentrations of DE-71 were based on previous in vitro studies [ 29 , 33 ], which exceeded PBDE levels found in the indoor environment in Denmark [ 10 ], as well as in the blood of Danish donors [ 22 , 34 ]. These studies showed correlations between PBDEs in dust and blood, suggesting that dust was a primary exposure source in humans.…”
Section: Discussionmentioning
confidence: 99%